RELEASE OF CLONE BT19 AND BT20 FOR POVERTY REDUCTION IN TEA SECTOR OF BANGLADESH - Hossain, M.I.; Ahmed, M.; Aziz, M.A.; Arefin, M.R.; Ashrafuzzaman, M. Ashrafuzzaman; Hossain, M.A. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Bangladesh is a country of 140 million populations where poverty reduction is the prior challenge. With a low level of per capita income, Bangladesh needs to formulate a multi-sectorial strategy for poverty reduction. As Bangladesh is an agricultural based country poverty can be minimized by enhancing agricultural inputs to maximize our production. Tea is an important cash crop in our country. Vast population directly or indirectly depends on our tea industry. The present study was conducted to investigate yield, quality and drought performance of the two newly released variety named BT19 and BT20 by Bangladesh Tea Research Institute. The experiment was conducted at Bangladesh Tea Research Institute experimental farm where four test clones namely Sh/D/11/313, A/8/8, A/17/7, A/22/39 and a well renowned Indian clone TV1 used as a control. The experimental result revealed that amongst the four test clones A/17/7 and A/8/8 are statistically more high yielder and drought tolerant than the control. A/17/7 is more high yielding than A/8/8 but A/8/8 is more drought tolerant. So considering yield, quality and drought potentials, the test clone A/17/7 and A/8/8 have recently released as BT19 and BT20 respectively which can be used as improved planting material in our tea growing areas by small growers and small holders to increase our production, quality as well as job opportunities and national income to eradicate our poverty.